Improving preterm infants' immunisation status: A follow‐up audit. (27th December 2013) - Crawford, Nigel W; Barfield, Charles; Hunt, Rod W; Pitcher, Helen; Buttery, Jim P
<x xml:space="preserve">Abstract</x> Aim Preterm infants are at increased risk of vaccine preventable diseases. An audit in 2007 identified suboptimal immunisation status of preterm infants. The aim of this study was to complete the 'audit loop', reviewing preterm infants' immunisation status at a single tertiary paediatric hospital. Methods A retrospective follow‐up immunisation audit was conducted at The Royal Children's Hospital, Melbourne, neonatal unit. The 'audit loop' included a preterm infants' reminder sticker and feedback of the original audit findings to Royal Children's Hospital health‐care professionals. Immunisation status was determined using the Australian Childhood Immunisation Register record for all admitted preterm infants born <32 weeks gestation (July 2008–June 2009). Results Conducted in March 2011, the median age of participants (n = 57) was 2.5 years (range 1.7–3.1 years). Forty‐four per cent (25/57) had a history of chronic lung disease, 86% (49/57) were <1500 g and 42% (24/57) <28 weeks gestation. The majority (96% (55/57)) were up to date with routine immunisations at 12 months of age. There was a 2.4‐fold increase, compared with the original audit, for receipt of the additional recommended hepatitis B vaccine at 12 months of age, as well as influenza vaccine in infants with chronic lung disease. Conclusion This study showed that a simple reminder combined with education strategies can improve vaccine delivery in special risk groups such as preterm infants.